CORRELATION OF Pb METAL ION LEVELS ON PROTEIN CONCENTRATION IN CRUSH CONSTRUCTION (Gafrarium tumidium) TAKEN IN THE COAST OF BONTANG, EAST KALIMANTAN - Corebima, Damianus Develistur; Kartika, Rudi; Hindryawati, Noor (JURNAL ATOMIK, 2020)
Research on the correlation of Pb metal ion levels to protein content in crush clams (Gafrarium tumidium) taken at the coast of the East Kalimantan Rhino Estuary has been conducted. This study aims to determine the levels of Pb metal ions and protein levels in blood clams based on the size and location of different samples. Correlation of Pb metal ion levels and protein in blood clams was tested using the Least Square method and Pearson product moment. Analysis of Pb metal ion levels using SSA (Atomic Absorption Spectrophotometer) and protein content analysis using the Kjeldahl method. In this study, the Pb metal ion level was obtained at the public port of Tanjung Limau, PPI Tanjung Limau and beach Lallo Sekangat with an average of 0.7474 mg/L, 0.5513 mg/L, and 0.2804 mg/L respectively. Crush clam protein content at Tanjung Limau, PPI Tanjung Limau and beach Lallo Sekangat with an average of 19.6544%, 14.6902%, and 10.9135% respectively. The correlation of Pb metal levels to protein levels in crush clams (Gafrarium tumidium) was stated positively with coefficient correlation results was strong (r = 0.7910).